Estudo dos distúrbios do sono em pacientes com distonia focal: blefaroespasmo - Lestingi, Silvia Cordova [UNIFESP] (2020)
Objective: We evaluated the quality of sleep and circadian rhythm in a sample of Brazilian blepharospasm patients. Methods: A total of 51 patients, who met the clinical criteria for blepharospasm, evaluated by two specialists in movement disorders, were recruited from the outpatient clinic for movement disorders of two reference centers in the city of São Paulo: Federal University of São Paulo and São Paulo Public Servants Hospital. The selected 13 patients were evaluated from 13 days before to 13 days after the use of botulinum toxin. They were interviewed, underwent physical examination and actigraphy, and completed sleep diaries. Results: Seven patients (58.8%) were at risk for developing obstructive sleep apnea syndrome (OSAS). The quality of sleep was poor for eight patients (61.5%) and showed a strong positive correlation coefficient with insomnia. After the use of botulinum toxin, the group that reported sleep improvement exhibited a 50% decrease in sleep latency. There was no change in the circadian rhythm. Patients who reported no sleep improvement after the use of botulinum toxin presented with poorer synchronization of the light-dark cycle. Conclusion: Blepharospasm patients present with poor sleep quality, displaying a strongly positive correlation with the insomnia severity index. About 50% of the patients presented with sleep improvement after using botulinum toxin. The synchronization of the light-dark cycle may influence this improvement.